Effects of carbonated drink as an extender on semen characteristics, fertility and hatchability in Nigerian Indigenous Chicken - Adebisi, Adeyina Oluwatoba (Journal of Agricultural Sciences (Belgrade), 2021)
AbstractCommercial carbonated drink (CD) as an extender was evaluated on semen characteristics, fertility and hatchability in Nigerian indigenous chicken (NIC). Under the condition of 370Celsius, 5% and 10% of CD were added to egg yolk citrate solution to make 100%. NIC cock semen were added to the extenders and preserved for 0, 30 and 60 minutes respectively in a factorial design layout. Percentage motility of sperm cells was significantly (p
Keywords: Key words: Semen, extender, carbonated drink, motility, Nigerian indigenous chicken.